2017
DOI: 10.1037/abn0000261
|View full text |Cite
|
Sign up to set email alerts
|

Explicit and implicit self-evaluations in social anxiety disorder.

Abstract: Cognitive models of social anxiety disorder (SAD) emphasize the role of explicit and implicit self-evaluations (SEs) in the etiology and maintenance of this condition. Whereas individuals with SAD consistently report lower explicit SEs as compared with nonanxious individuals, findings concerning implicit SEs are mixed. To gain a more nuanced understanding of the nature of SEs in SAD, we examined explicit and implicit SEs in two significant interpersonal domains: social rank and affiliation. Consistent with cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 43 publications
(52 reference statements)
0
15
0
Order By: Relevance
“…Theoretically, individuals with heightened (versus low) symptoms of social anxiety disorder (SAD) should demonstrate relatively more negative self + social associations; however, empirically, the literature is quite mixed (see the review in Roefs et al 2011). Gilboa-Schechtman et al (2017) recently argued that the inconsistent findings are partly due to the fact that there are different types of self-evaluations, which vary in importance for socially anxious individuals. For example, when a Single Category IAT was used, individuals with SAD (versus nonclinical control individuals) demonstrated relatively weaker implicit self-evaluations tied to social rank (e.g., self + dominant; Gilboa-Schechtman et al 2017).…”
Section: Anxiety: Empirical Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Theoretically, individuals with heightened (versus low) symptoms of social anxiety disorder (SAD) should demonstrate relatively more negative self + social associations; however, empirically, the literature is quite mixed (see the review in Roefs et al 2011). Gilboa-Schechtman et al (2017) recently argued that the inconsistent findings are partly due to the fact that there are different types of self-evaluations, which vary in importance for socially anxious individuals. For example, when a Single Category IAT was used, individuals with SAD (versus nonclinical control individuals) demonstrated relatively weaker implicit self-evaluations tied to social rank (e.g., self + dominant; Gilboa-Schechtman et al 2017).…”
Section: Anxiety: Empirical Evidencementioning
confidence: 99%
“…Gilboa-Schechtman et al (2017) recently argued that the inconsistent findings are partly due to the fact that there are different types of self-evaluations, which vary in importance for socially anxious individuals. For example, when a Single Category IAT was used, individuals with SAD (versus nonclinical control individuals) demonstrated relatively weaker implicit self-evaluations tied to social rank (e.g., self + dominant; Gilboa-Schechtman et al 2017). In contrast, there was not a significant group difference on implicit self-evaluations tied to social affiliation (e.g., self + friendly).…”
Section: Anxiety: Empirical Evidencementioning
confidence: 99%
“…Previous studies have indicated that SAD-patients experience disturbances in self-referential processing and have biases concerning the opinion of others about them: they have increased self-portrayal concerns [9], for example when it concerns their social rank [10, 11] or their own social performance [12, 13], they overestimate the negative consequences of their own social blunders [14] and are characterized by negatively biased learning about themselves from social feedback [15]. Furthermore, clinical SAD is associated with an increased belief in negative interpretations of social situations [16] and SAD-patients focus predominantly on potentially embarrassing events when they evaluate themselves in a social context [17].…”
Section: Introductionmentioning
confidence: 99%
“…The two sub-scales of the Hebrew LSAS have demonstrated high internal (.91) and test-retest (.87-.96) reliability and strong discriminant validity among Israeli adults with social anxiety or panic disorders (Levin, Marom, Gur, Wechter, & Hermesh, 2002). Internal consistency reliability of the whole scale in a clinical Israeli sample was .97 (Gilboa-Schechtman et al, 2017).…”
Section: Methodsmentioning
confidence: 98%
“…In a meta-analysis of 144 studies, internal consistency reliability of the BDI was .89, test-retest reliability was .75, and convergent comparisons were robust across 43 depression instruments (Erford, Johnson, & Bardoshi, 2015). Prior internal consistency reliabilities of the Hebrew BDI among Israeli samples range between .84 and .92 (Daie-Gabai et al, 2011;Gilboa-Schechtman et al, 2017).…”
Section: Methodsmentioning
confidence: 99%